Molecular cloning of 3-hydroxy-3-methylglutaryl coenzyme a reductase and evidence for regulation of its mRNA. - Chin, D J (Proc Natl Acad Sci U S A, 1982)
A recombinant plasmid containing a 1.2-kilobase cDNA for 3-hydroxy-3-methylglutaryl coenzyme A reductase was isolated from a cDNA library prepared from UT-1 cells, a clone of Chinese hamster ovary cells that has markedly elevated reductase activity. This plasmid, designated pRed-10, was identified by differential colony hybridization and hybrid-selected mRNA translation. The mRNA that hybridized to pRed-10 directed the synthesis in vitro of a 90,000-dalton protein that was immunoprecipitated by an antireductase antibody. The same 90,000-dalton protein was immunoprecipitated when UT-1 cells were pulse labeled with [35S]methionine in vivo and rapidly solubilized with boiling NaDodSO4. By blot hybridization, pRed-10 hybridized to mRNAs of 4.2 and 4.7 kilobases in UT-1 cells. Both mRNAs were reduced to undetectable levels when low density lipoprotein, a suppressor of the reductase, was present in the culture medium. These data indicate that the primary translation product of reductase mRNA is a 90,000-dalton protein and that LDL suppresses the reductase in UT-1 cells by drastically reducing the level of its mRNA. IMAGES: